Comparative effectiveness of water and salt community‐based fluoridation methods in preventing dental caries among schoolchildren. Issue 6 (28th July 2016) - Fabruccini, A.; Alves, L.S.; Alvarez, L.; Alvarez, R.; Susin, C.; Maltz, M.
Abstract: Objective: To compare the effectiveness of water and salt community‐based fluoridation methods on caries experience among schoolchildren. Methods: Data derived from two population‐based oral health surveys of 12‐year‐old schoolchildren exposed to different community‐based fluoridation methods were compared: artificially fluoridated water in Porto Alegre, South Brazil and artificially fluoridated salt in Montevideo, Uruguay. Data on socio‐demographic characteristics, maternal education and oral hygiene were collected. Dental caries was defined according to the WHO criteria (cavitated lesions) and to the modified WHO criteria (active noncavitated lesions and cavitated ones). The association between community‐based fluoridation methods and dental caries was modelled using logistic (caries prevalence) and Poisson regression (DMFT). Odds ratios (OR), rate ratios (RR), and the 95% confidence intervals (CI) were estimated. Results: A total of 1528 in Porto Alegre and 1154 in Montevideo were examined (response rates: 83.2% and 69.6%, respectively). Adjusted estimates for caries prevalence and DMFT showed that schoolchildren from Porto Alegre were less affected by dental caries than their counterparts from Montevideo, irrespective of the criteria used. After adjusting for important characteristics, schoolchildren exposed to fluoridated salt had significantly higher likelihood of having caries (WHO criteria) than those exposed to fluoridated water (OR for prevalence=1.61, 95% CI=1.26–2.07; RR for DMFT=1.32, 95% CI=1.16–1.51). Similar differences were observed using the modified WHO criteria. Conclusion: Fluoridated water appears to provide a better protective effect against dental caries than fluoridated household salt among schoolchildren from developing countries.